Development and evaluation of quality characteristics of egg balls. Issue 6 (4th November 2014) - Goswami, Meena; Pathak, Vikas; Bharti, Sanjay; Singh, Veer; Singh, Tanuja; Sengar, Abhishek
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The present study was aimed to enhance the nutritional quality of veg bottle gourd balls by incorporating boiled mashed egg replacing bottle guard in the formulation of batter. Design/methodology/approach – Three different levels, viz. 50, 60 and 70 per cent of boiled mashed whole egg were taken to optimize the level of egg in veg balls by replacing the bottle gourd. The developed products were evaluated for physico-chemical, proximate analysis and sensory evaluation on Day 0, 3, 6 and 9 of storage, whereas microbiological studies of the product were conducted on Day 1, 4, 7 and 10. Findings – The pH, cooking yield and weight gain were non significantly higher in egg-incorporated balls as compared to control. Similar trends were observed for mean Thio Barbituric Acid (TBA) and free fatty acid (FFA) values, however, the estimated values remained within the acceptable limit throughout the storage period. Mean protein and fat content were significantly (p < 0.05) higher and the moisture content was significantly lower (p < 0.05) in egg-incorporated balls. There was no significant difference for mean Total Plate Count, Yeast and mould count and Psychrophillic count between the treatments and control during storage except at later stage on Day 7 and 10. The mean sensory scores were found to be the highest for egg balls, with 60 per cent boiled mashed whole egg for all sensory attributes and the flavor was very much liked by the sensory panelists. Research limitations/implications – The trials can be further carried out for some color and properties, with the addition of various antioxidants and antimicrobial agents. Originality/value – Veg bottle gourd balls are a very much relished delicacy of Indian culinary practices. The incorporation of egg not only enhanced the nutritional properties, also improved the flavor and consumer acceptance. It can be a very good alternative to cope up with malnutrition and hunger.